Victimization Prevention and Awareness on College Campuses: Interconnection Between Title IX and #MeToo - Azimi, Andia M. (American journal of criminal justice, 2021)
The #MeToo movement centers on raising awareness of risky situations for victimization and encourages the general community to intervene in these situations. Similarly, sexual violence awareness programming that take place on college campuses throughout the academic year can prime individuals to be active bystanders. Except for a handful of systematically evaluated bystander intervention programs, however, it is unclear how informal sexual violence awareness programming affects actual intervention behaviors. The link between prior victimization and bystander intervention is also not well understood. Given these gaps in research, the current study examines how exposure to sexual violence awareness programming and prior victimization are associated with bystander intervention. In particular, we consider the intersection of prior sexual victimization and participating in sexual violence awareness programming on campus. Utilizing a sample of 735 college students from a four-year southeastern university, the results of the current study demonstrate victims of sexual violence who attend sexual violence awareness programming are less likely to intervene. The findings of the current study highlight the importance of program design and suggest that increased attention to the problem of sexual violence does not necessarily translate into bystander intervention. Overall, this may run counter to goals of the #MeToo movement and deserves further attention. Avenues for future research are discussed.